Brave the dark [videorecording (DVD)] - Harris, Damian, 1958-; Bradley, Dale G.; Hay, L. R. (Lynn Robertson); Deen, Nathaniel; Spencer, John P.; Harris, Jared, 1961-; Segal, Tobias; Hamilton, Nicholas, 2000- (Angel Studios, 2025)
Haunted by torturous childhood memories, Nate Williams finds himself engulfed in darkness. When his drama teacher, Mr. Deen bails him out of jail and takes him in, Nate must confront his past before it leads to his own destruction.